Pengabdian Masyarakat Berbasis Live-In di Stasi Wiwipemo - Fransiskus Saverius Minggu; Yulianus Kian; Jefrianus Ulu Manek; Paskalis Jhon Juang; Frederikus rifaldo Soro; Robertho Mario Wetan Kwure (Jurnal Pengabdian Masyarakat, 2026)
Community Service based on the Live-In approach is a model of engagement that emphasizes living together with the community as a concrete form of student involvement in social, cultural, and pastoral realities. This activity was carried out by students of the Institute of Philosophy and Creative Technology (IFTK) Ledalero at Wiwipemo Station, Maria Immaculata Jopu Parish, Archdiocese of Ende, during the New Year celebration. The program aimed to foster students’ social and pastoral sensitivity, strengthen fraternal relationships with the local community, and support ecclesial life through direct participation in social, liturgical, and pastoral activities. The methods applied included the live-in method, participatory approach, direct pastoral accompaniment, and collaborative engagement with local community groups. The results indicate the establishment of close and trustful relationships between students and the community through the foster-family system, increased community participation in liturgical and communal activities, and the enrichment of students’ pastoral experience by integrating academic reflection with practical service. This activity affirms that community service is not merely program-oriented but is fundamentally a process of encounter, solidarity, and shared faith formation within the life of the local Church.